2016
DOI: 10.1089/gtmb.2015.0341
|View full text |Cite
|
Sign up to set email alerts
|

Association of MSX1 c.*6C > T Variant with Nonsyndromic Cleft Lip With or Without Cleft Palate in Turkish Patients

Abstract: Our identification of the c.*6C > T variant appears to be the first reported result associating variants of the MSX1 gene with nsCL/P patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The rs12532 SNP was the most widely investigated SNP (seven studies, HWE P > 0.05 among the controls), followed by rs8670, rs6446693, rs104893854, rs3775261, and rs1907998 [three studies each; HWE P > 0.05, except for rs8670 in the study by Aslar Oner et al . , rs6446693 in the study by Sun et al . , rs104893854 in the study by Huang et al .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The rs12532 SNP was the most widely investigated SNP (seven studies, HWE P > 0.05 among the controls), followed by rs8670, rs6446693, rs104893854, rs3775261, and rs1907998 [three studies each; HWE P > 0.05, except for rs8670 in the study by Aslar Oner et al . , rs6446693 in the study by Sun et al . , rs104893854 in the study by Huang et al .…”
Section: Resultsmentioning
confidence: 93%
“…Among these studies, six were performed in Asian populations (6,(19)(20)(21)(22)(23), three were performed in Caucasian populations (24)(25)(26), and the remaining three were performed in Mexican and Brazilian subjects, who were grouped as South American (18,27,28). Three studies (6,21,25) performed a stratified analysis of CL/P and CPO and provided detailed genotype information for the SNPs in these two subgroups (6,21,25).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…HWE was assessed using the online application, https://ihg.gsf.de/cgi-bin/hw/hwa1.pl. Screening for HWE resulted in exclusion of two articles (Aslar Oner & Tastan, ; Rochmah, Suwarsi, & Harumsari, ) which we detail in S1 List B. With a median and interquartile range of 8.0 (6.25–8.75) for the non‐normally distributed CB scores (Shapiro–Wilk test: p = 0.02), methodological quality of the component studies was high (Table ).…”
Section: Resultsmentioning
confidence: 99%
“… we excluded the study (Aslar Oner & Tastan, ) because our calculations showed that their control frequencies deviated from the Hardy–Weinberg Equilibrium (S1 List B). …”
Section: Methodsmentioning
confidence: 99%